SISTEM ALARM PADA KOTAK OBAT BERBASIS ARDUINO UNO - Wijayanti, Linda; Mulyadi, Melisa; Ghozali, Theresia; Joevierdi, Joevierdi (Universitas Tarumanagara, 2023)
The right schedule for taking medication according to the frequency given by the doctor is one of the success factors of the treatment process. However, due to the patient's busy schedule and physical limitations of the patient as well as in the case of the elderly who are unable to carry out their normal activities, it is necessary to remind them to take medication regularly according to the doctor's prescription. The research method uses the waterfall model, which was developed by Pressman. The alarm system in this medicine storage box is designed to dispense medicine and sound an alarm at a predetermined time. Users only need to enter the medicine to be consumed by setting the frequency and time of the alarm. This system uses a real-time clock connected to the Arduino Uno microcontroller. The system data input comes from the matrix keypad to enter the alarm time and the light sensor to detect the presence of medicine. The output of the microcontroller controls the buzzer as an alarm and the solenoid valve to open the box containing the medicine to be taken at a pre-programmed time. From the test results obtained that the device can dispense medicine according to the frequency and time of the alarm that has been determined by the user. Keywords: alarm; medicine storage box; Arduino Uno; real time clock Abstrak Jadwal minum obat yang tepat sesuai frekuensi yang diberikan dokter merupakan salah satu faktor keberhasilan dari proses pengobatan. Namun karena kesibukan dan keterbatasan fisik pasien maupun pada kasus lansia yang sudah tidak dapat beraktivitas secara normal, diperlukan pengingat waktu minum obat secara rutin sesuai resep dokter. Metode penelitian menggunakan model waterfall, yang dikembangkan oleh Pressman. Sistem alarm pada kotak obat ini dirancang untuk mengeluarkan obat dan membunyikan alarm pada waktu yang telah ditentukan. Pengguna hanya perlu memasukkan obat yang akan dikonsumsi dengan mengatur frekuensi dan waktu alarm. Sistem ini menggunakan real time clock yang terhubung ke mikrokontroler Arduino Uno. Masukan data sistem berasal dari keypad matrix untuk memasukkan waktu alarm dan sensor cahaya untuk mendeteksi adanya obat. Keluaran mikrokontroler mengendalikan buzzer sebagai alarm dan katup solenoida untuk membuka kotak yang berisi obat yang akan diminum pada waktu yang telah diprogram sebelumnya. Dari hasil pengujian diperoleh bahwa alat dapat mengeluarkan obat sesuai dengan frekuensi dan waktu alarm yang telah ditentukan oleh pengguna.